Gadolinium Manganese Oxide Nanorod Catalyst via a Facile Hydrothermal Approach: Application for Voltammetric Sensing of Antibiotic Drug Rifampicin in Pharmaceutical and Biological Samples. Issue 5 (1st May 2022) - Pulikkutty, Subramaniyan; Manjula, Natesan; Chen, Tse-Wei; Chen, Shen-Ming; Al-onazi, Wedad A.; Al-Mohaimeed, Amal M.; Hsu, Heng-Yuan; Huang, Chun-Wei; Yu, Ming-Chin; Elshikh, Mohamed S
Abstract : This study constructs a rough-surfaced rod structure of gadolinium manganese oxide fabricated by a glassy carbon electrode (GMO NRs/GCE). The resulting nanostructure was applied as an efficient electrocatalyst for the antibiotic drug rifampicin (RIF) sensor. In addition to the crystal structure study by X-ray diffraction (XRD), morphology study by Field Emission Scanning Electron Microscope (FESEM), Transmission electron microscopy (TEM), and the functional group examined by Fourier transform infrared spectroscopy (FTIR), elemental state study by X-ray photoelectron spectroscopy (XPS). As-synthesized samples were characterized systematically by electrochemical methods including cyclic voltammetry (CV), differential pulse voltammetry detection (DPV), and electrochemical impedance spectroscopy (EIS). The improving electrochemical behaviors of GMO NRs could be ascribed to the outstanding electrocatalytic activity with the high surface area and good conductivity. Under the experimental conditions, the quantitative measurement of RIF resulted in a large and wide linear range of 0.15 to 136.15 μ M, a low detection limit was calculated to be 0.071 μ M. The sensor had good selectivity, reproducibility, and high stability. Importantly, the GMO NRs sensor was effectively applied to determine RIF in serum, urine, and pharmaceutical samples with satisfactory accuracy and recovery.